Beginning Course Surveys: Bridges for Knowing and Bridges for Being - Starr-Glass, David (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
The use of a participant survey, administered at the outset of an online course, can provide information useful in the management of the learning environment and in its subsequent redesign. Such information can clarify participants’ prior experience, expectations, and demographics. But the very act of enquiring about the learner also signals the instructor’s social presence, relational interest, and desire to enter into an authentic dialogue. This study examines the use of participant surveys in online management courses. The first section discusses the informational bridges that this instrument provides. The second section considers survey responses to open-ended questions dealing with student sentiments. This analysis suggests that the survey plays a valuable part in accentuating social presence and in initiating relational bridges with participants.